Macroeconomic dynamics under bounded rationality: on the impact of consumers' forecast heuristics - Tae-Seok Jang; Stephen Sacht (Journal of Economic Interaction and Coordination, 2022)
This paper considers various types of forecast heuristics to examine the effects of boundedly rational agents on macroeconomic dynamics. Given the baseline New Keynesian model, we seek to find the expectation formation process that is most suitable in describing economic adjustments over the business cycle. In particular, impulse response analysis is used to compare the performances of the macroeconomic model under bounded rationality and under rational expectations. The results show that the fluctuations in consumer confidence mainly explain the degree of persistence in consumption. We conclude that a model under bounded rationality with a heuristic-induced switching process can qualitatively provide a good fit to the data that is equivalent to a model under rational expectations.
Keywords: C53; D83; E12; E21; E32; 330; Bounded rationality; Consumer confidence; Forecast heuristics; Impulse response analysis; New Keynesian model